In situ high-temperature Raman spectroscopy for online EAF slag analysis - Bohong Zhang; Hanok Tekle; Ronald J. O'Malley; Jeffrey D. Smith; Farhan Mumtaz; Jie Huang (Journal of Materials Research and Technology)
Real-time monitoring of slag chemistry is critical for optimizing Electric Arc Furnace (EAF) steelmaking operations, where dynamic variations in slag composition directly influence slag foaming, refractory degradation, and thermal efficiency. Conventional techniques such as X-ray fluorescence (XRF), Fourier-transform infrared (FTIR), and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) are commonly used to analyze slag composition, but their offline nature and equipment constraints limit their applicability for online monitoring in harsh industrial environments. To address this challenge, we present an in situ, high-temperature analytical approach that integrates Raman spectroscopy with a custom-designed fiber-optic probe for real-time slag characterization at 1550 °C. The system enables non-destructive spectral acquisition from molten slags, providing molecular-level insights into silicate polymerization and iron oxidation states. Eight synthetic slag samples were evaluated, and key Raman features—such as Qn silicate units and FeO4/FeO6 coordination environments—were identified and quantitatively correlated with slag basicity and Fe2O3 content. The results demonstrate agreement between Raman spectral ratios and bulk slag chemistry, validating the method's capability to track compositional and structural changes under molten temperature. This work establishes the feasibility of deploying fiber-optic Raman probe for online EAF slag monitoring and highlights their potential to support closed-loop control strategies, thereby enhancing process stability, refractory protection, and steel quality in industrial steelmaking applications.